2021
DOI: 10.1101/2021.11.16.21266121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cumulative Effects of Resting-state Connectivity Across All Brain Networks Significantly Correlate with ADHD Symptoms

Abstract: BackgroundThe clinical utility of MRI neuroimaging studies of psychopathology has been limited by a constellation of factors—small sample sizes, small effect sizes, and heterogeneity of methods and samples across studies—that hinder generalizability and specific replication. An analogy is early genomics studies of complex traits, wherein a move to large, multi-site samples and a focus on cumulative effects (polygenic scores) led to reproducible and clinically applicable effects from genome-wide association stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…61 Similarly, there was no convergence in the spatial patterns of functional brain connectivity associated with ADHD in the literature, 17 and ADHD traits have been reported to be more associated with brainwide connectivity than with local connectivity. 62 Thus, our findings support the distributed involvement of brain regions in intelligence and hyperactivity and impulsivity symptoms.…”
Section: Jama Network Open | Imagingsupporting
confidence: 78%
“…61 Similarly, there was no convergence in the spatial patterns of functional brain connectivity associated with ADHD in the literature, 17 and ADHD traits have been reported to be more associated with brainwide connectivity than with local connectivity. 62 Thus, our findings support the distributed involvement of brain regions in intelligence and hyperactivity and impulsivity symptoms.…”
Section: Jama Network Open | Imagingsupporting
confidence: 78%
“…As mathematical description of these processes rapidly improves, targeted intervention should improve as well 8 . Further, clinical algorithms could utilize composite scores reflecting system-wide activity in brain, such as a polyvertex score (Zhao et al, 2019) or related score for functional networks (Mooney et al, 2021), or epigenetic or physiological summary scores (Stevenson et al, 2020). These would target regulatory process and could become indices of clinical change (the complexity of interpreting poly-scores notwithstanding).…”
Section: Part 2: Sketch Of the Theory And Hypothesesmentioning
confidence: 99%
“…Furthermore, following the polygenic scores in the field of genetics, recently, the use of polyneuro scores has been proposed (Mooney et al, 2021). Polyneuro scores are summary scores of the cumulative effect of brainwide measures that capture effects across widely distributed brain systems and regions that are involved in different human traits (Mooney et al, 2021). Applied to ADHD, Mooney et al (2021) showed that such summary scores of functional connectivity across the brain have increased predictive power for ADHD symptoms.…”
Section: Brain-wide Association Studiesmentioning
confidence: 99%
“…Polyneuro scores are summary scores of the cumulative effect of brainwide measures that capture effects across widely distributed brain systems and regions that are involved in different human traits (Mooney et al, 2021). Applied to ADHD, Mooney et al (2021) showed that such summary scores of functional connectivity across the brain have increased predictive power for ADHD symptoms. The scores explained around 8 times more variation than the variation explained by the most significant connection in the brain.…”
Section: Brain-wide Association Studiesmentioning
confidence: 99%